Children road traffic injuries in Poland - Goniewicz, Krzysztof; Goniewicz, Mariusz; Pawłowski, Witold; Fiedor, Piotr (Polish Journal of Public Health, 2017)
Road traffic injuries are the leading cause of child mortality in Poland, resulting in more deaths than cancer or birth defects. We present the main problems of road safety and the nature of the causes and consequences of accidents among children based on the World Health Organization Report. Children injuries are one of the main problems in modern medicine requiring vigorous and preventive actions. Children of all ages should be intensively involved in the educational activities related to road safety.Raising awareness concerning the risks associated with children’s participation in traffic as well as the awareness of parents and carers can greatly reduce the number of accidents.